What Drives Purchase Intention on Adira Finance Leasing Karawang? - Savitri, Citra; Triadinda, Dexi; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The problem in this research is high online shopping behavior and the use of social media in providing information related to the desired product. The change in behavior has a direct impact on decreasing motorcycle purchases. The role of social media as informants gives influence to society at large. This study aims to obtain empirical evidence and find out how the influence of Online Review and Rating on Interest in motorcycle purchases at Adira Finance Karawang. The phenomenon and conclusions about the influence of Online review. The method used in this research uses descriptive methods and quantitative approaches with a sample of 115 respondents. The sampling technique used in this research is simple random sampling with Path Analysis. Based on the results of this research indicate that Online Consumer Review and Rating of Purchase Intention have a significant influence and have a good relationship between variables. This research can contribute to leasing companies to determine the right promotional strategy for business.